THE PERCEIVED ROLE OF LEADERSHIP IN PROFESSIONAL ASSISTANCE OF SECONDARY SCHOOL TEACHERS - Aziz, Fakhra; Quraishi, Uzma; Nader , Moafia; Latif, Naila (International Journal of Psychosocial Rehabilitation, 2020)
This study intended to explore the perceived role of leadership in professional assistance of secondary school teachers. five secondary schools from public sector and five from private sector were randomly selected. ten teachers including newly inducted and experienced from each school were purposively selected for data collection. a questionnaire for survey, tpas was developed to collect data for teachers’ professional assistance. to find out relationship between various research variables chi-square test for independence was used. results revealed significant role of school heads in teachers’ professional assistance although secondary school teachers were found to be more facilitated by their heads for their instruction. the present study suggests an active, and more facilitating role of school heads in teachers’ professional and emotional aspects of assistance. further, active and effective leadership practices of professional assistance by heads for quality performance of teachers are required in order to uplift the overall education.